Son of a gun - De Graaf, Anne (Eerdmans Books for Young Readers, 2012)
Eight-year-old Liberian Lucky, his ten-year-old sister Nopi, and their schoolmates are kidnapped and forced to become child soldiers, but even after they escape along with some other children and are reunited with their parents, their lives will never be the same. Includes chapter about Liberia.